Principals' perceptions on the practice of distributed leadership: a quantitative study - García Carreño, Ingrid del Valle (Revista Ibero-Americana de Estudos em Educação, 2018)
The aim of this paper is to describe distributed leadership practices (DLP) in order to know the point of view of the directors of primary education centers of the Community of Madrid, Spain. It has been framed in a quantitative methodology, and a descriptive study, with a pilot test; also, it has been constructed and validated the ad hoc questionnaire "Distributed leadership practices of the Principal school", that allows collecting the perception that develops the directors (as) in the context studied, and to know the relevance that they grant to them. The results found are very broad and correspond to the set of directors (as) surveyed. This research presents the results of the DLP, which refers to the responses given by the group of school directors in one of the four dimensions (DLP, Shared Decisions, Mission, Vision and Professional Development).